Quantitative Analysis of Piperine from Ayurvedic Polyherbal Formulations using Reverse Phase High Performance Liquid Chromatography - SUNITA S; S. N. MENON; A. SINGH (International Journal of Pharma and Bio Sciences, 2010)
A simple, rapid and precise reverse-phase high performance liquid chromatographic method has been developed for the quantitative determination of piperine from Ayurvedic Polyherbal formulations Arkavati, Krvyadras and Marichyadi taila. Chromatographic analysis was carried out on cosmosil C18 column (150mm x 4.6mm, 5µm particle) with a mobile phase of methanol: water in the volume ratio of 70:30 at a flow rate of 1.0 mL min-1. Quantitation was performed using a PDA-detector at 342 nm. Linear response for piperine was obtained over a range of 200 to 3000 ng mL-1. The method was validated for linearity, precision, accuracy and can be effectively used to evaluate quality of Arkavati, Krvyadras and Marichyadi taila.